Cytokine Hemoadsorption During Cardiac Surgery Versus Standard Surgical Care for Infective Endocarditis (REMOVE): Results From a Multicenter Randomized Controlled Trial. Issue 13 (25th February 2022) - Diab, Mahmoud; Lehmann, Thomas; Bothe, Wolfgang; Akhyari, Payam; Platzer, Stephanie; Wendt, Daniel; Deppe, Antje-Christin; Strauch, Justus; Hagel, Stefan; Günther, Albrecht; Faerber, Gloria; Sponholz, Christoph; et al.
Abstract : Background: Cardiac surgery often represents the only treatment option in patients with infective endocarditis (IE). However, IE surgery may lead to a sudden release of inflammatory mediators, which is associated with postoperative organ dysfunction. We investigated the effect of hemoadsorption during IE surgery on postoperative organ dysfunction. Methods: This multicenter, randomized, nonblinded, controlled trial assigned patients undergoing cardiac surgery for IE to hemoadsorption (integration of CytoSorb to cardiopulmonary bypass) or control. The primary outcome (change in sequential organ failure assessment score [ΔSOFA]) was defined as the difference between the mean total postoperative SOFA score, calculated maximally to the 9th postoperative day, and the basal SOFA score. The analysis was by modified intention to treat. A predefined intergroup comparison was performed using a linear mixed model for ΔSOFA including surgeon and baseline SOFA score as fixed effect covariates and with the surgical center as random effect. The SOFA score assesses dysfunction in 6 organ systems, each scored from 0 to 4. Higher scores indicate worsening dysfunction. Secondary outcomes were 30-day mortality, duration of mechanical ventilation, and vasopressor and renal replacement therapy. Cytokines were measured in the first 50 patients. Results: Between January 17, 2018, and January 31, 2020, a total of 288 patients were randomly assigned to hemoadsorption (n=142) or control (n=146). Four patients in the hemoadsorption and 2 in the control group were excluded because they did not undergo surgery. The primary outcome, ΔSOFA, did not differ between the hemoadsorption and the control group (1.79±3.75 and 1.93±3.53, respectively; 95% CI, –1.30 to 0.83; P =0.6766). Mortality at 30 days (21% hemoadsorption versus 22% control; P =0.782), duration of mechanical ventilation, and vasopressor and renal replacement therapy did not differ between groups. Levels of interleukin-1β and interleukin-18 at the end of integration of hemoadsorption to cardiopulmonary bypass were significantly lower in the hemoadsorption than in the control group. Conclusions: This randomized trial failed to demonstrate a reduction in postoperative organ dysfunction through intraoperative hemoadsorption in patients undergoing cardiac surgery for IE. Although hemoadsorption reduced plasma cytokines at the end of cardiopulmonary bypass, there was no difference in any of the clinically relevant outcome measures. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03266302.